A new parasitic plant mite (Acari: Eriophyoidea) found on Trewia nudiflora L. (Euphorbiaceae) from India - Sanjay Sarkar (International Journal of Agriculture System, 2025)
During the periodical surveys for plant mite in the area of the Gangetic Plain of India, a new species eriophyoid mite, Ditilomiopus trewiacolous sp. nov. of the family Ditilomiopidae is found on the lower surface of the leaves of Trewia nudiflora. Trewia nudiflora L. belonging to family Euphorbiaceae, is an important medicinal plant, grows in moist tropical and semi- evergreen forests as well as non-forest areas of India and its neighbouring countries, Bangladesh, China, and Malaysia. The plant is attacked by a tiny sap sucking parasitic mite belonging to the superfamily Eriophyoidea of subclass Acari of class Arachnida and produces severe damage to the host. This new parasitic mite species is collected and processed for microscopic study and finally described with sufficient illustrations following standard taxonomic procedure. The relationship to the host plant is also described here. A comparative study of this mite with other previously known species has been conducted. After proper taxonomic diagnosis, it is found that this parasitic mite appears as new to Science from India. New name with its etymology has been given to this mite species following the Rules of International Code of Zoological Nomenclature and also registered in Zoo-Bank account to create unique ID: LSID urn: lsid: zoobank.org:pub:3BC0363B-160B-46CE-B9DA- 20864762AD10. This study may be helpful to the plant protection departments and may provide the basis of further research including DNA barcoding and systematic evolution. This research finding may also be helpful to the students of Pharmacology and Medicinal Botany.